Best practice in radiation oncology: A project to train the trainers: Review of 2008–2023 - Mary Coffey; Colleen Dickie; Elena Fidarova; Velimir Karadža; Philipp Scherer; Michelle Leech (Technical Innovations & Patient Support in Radiation Oncology)
The European Society of Radiotherapy and Oncology (ESTRO) and the International Atomic Energy Agency (IAEA) project on ‘best practice in radiation oncology: a project to train the radiation therapist trainers’ commenced in 2008.The aim of the project was to influence education programmes throughout, mainly, eastern Europe to increase the radiation therapy-specific education of their programmes. This is to enable graduates of these programmes to be radiation therapists that are fit for purpose in the clinic. This paper provides an update on the successes of the project to date, the challenges that remain and the new approaches to project delivery by the faculty over this period.